A system approach to improving guideline-directed therapy for cardio-renal-metabolic conditions: The "beyond diabetes" initiative - Benjamin J. Hirsh; Jamie S. Hirsch; Hosam Hmoud; Spencer Weintraub; Agnes Cha; Martin Lesser; Xueqi Huang; Yan Yan Sally Xie; Rachel Nahrwold; John Joshua; Jennifer Scanlon; Thomas Galella; et al. (Elsevier, 2023)
Objective: Despite demonstrating improvements in cardiovascular disease, kidney disease, and survival outcomes, guideline-directed antihyperglycemic medications such as sodium-glucose cotransporter 2 inhibitors (SGLT2i) and glucagon-like-peptide-1 receptor agonists (GLP1-RA), are underutilized. Many obstacles constrain their use including lack of systematic provider and patient education, concern for medication side effects, and patient affordability. Methods: We designed a multimodality, systems-based approach to address these challenges with the goal of increasing medication utilization across the largest healthcare system in New York State. This multispecialty collaborative included provider and patient education, an electronic health record-enabled platform to identify eligible patients, and access to pharmacists for medication guidance and addressing insurance coverage barriers. Surveys were administered following grand rounds lectures and knowledge-based questionnaires were given before and after case-based sessions for housestaff, with results analyzed using a two-sided Student's t-test. Rates of first prescriptions of SGLT2i/GLP1-RA in combined and individual analyses were compared between the pre- and post-education periods (6 months prior to 3/31/2021 and 6 months post 8/19/2021), and the change in prescriptions per 100 eligible-visits was assessed using the incidence density approach. Results: Among grand rounds participants, 69.3% of respondents said they would make changes to their clinical practice. Knowledge increased by 14.7% (p-value <0.001) among housestaff following case-based sessions. An increase in SGLT2i/GLP1-RA prescribing was noted for eligible patients among internal medicine, cardiology, nephrology, and endocrinology providers, from 11.9 per 100 eligible visits in the pre-education period to 14.8 in the post-education period (absolute increase 2.9 [24.4%], incidence risk ratio 1.24 [95% CI 1.18-1.31]; p-value <0.001). Increases in prescribing rates were also seen among individual medical specialties. Conclusions: Our "Beyond Diabetes" initiative showed an improvement in provider knowledge-base and was associated with a modest, but statistically significant increase in the use of SGLT2i and GLP1-RA throughout our healthcare system.